Exploring The Relationship of Grit Personality and Academic Achievement: Adult Learners - bt Abbas, Lutfiah Natrah; Binti Yusof , Amira Raihan; bt Ali, Azita (Online Journal for TVET Practitioners, 2023)
Grit is defined to the individual’s level of perseverance and motivation to achieve their long-term goals. The grit can drive students to sustain and finish their study in the time frame allocated. The purpose of this study is to determine the level of students’ grit among part time learners in Technical University in Malaysia and to explore how the grit level difference based on the gender. The study used the descriptive analysis approach. The sample of the study consisted of 148 students, who studied part time (via online), distributed as follows: (95) male and (53) female. To achieve the objectives of the study, an original grit scale (Grit-O) from Duckworth et al. (2007) was utilized. The results of the study revealed that the level of grit of the students were high, and the Grit level of male students were higher than female students. The study concluded that it is important build a strong grit character in students’ mind to have an outstanding academic achievement.